2004
DOI: 10.1093/sleep/27.4.701
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Parasomnias in Preadolescent School-aged Children: a Turkish Sample

Abstract: These results suggest that the prevalence of parasomnias was high in the 9- and 10-year-old age groups. Parasomnias are associated with a history of physical illness and neurobehavioral abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 0 publications
7
31
2
4
Order By: Relevance
“…The absolute prevalence rates obtained in this study lies within the range of figures reported in the literature, nevertheless immediate comparison to other studies is not possible because each study used different definitions of nightmares, for example, [3] applied the complete criteria of the nightmare disorder of the DSM IV [4]. In addition, answering categories differed across the studies: In this study sometimes/often were presented to the participants whereas in the Simonds and Parraga [36] study the cutoff was once a week.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The absolute prevalence rates obtained in this study lies within the range of figures reported in the literature, nevertheless immediate comparison to other studies is not possible because each study used different definitions of nightmares, for example, [3] applied the complete criteria of the nightmare disorder of the DSM IV [4]. In addition, answering categories differed across the studies: In this study sometimes/often were presented to the participants whereas in the Simonds and Parraga [36] study the cutoff was once a week.…”
Section: Discussionsupporting
confidence: 53%
“…Many large-scaled surveys [3,30,36,41] are based on questionnaires or interviews completed by the child's parents. Several studies [17,23,24,[26][27][28], however, reported a marked underestimation of nightmare occurrence in the parents' responses in comparison to the answers of the child, so that epidemiological studies based on data obtained from the parents have to be interpreted with caution.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,[16][17][18][19] The literature has demonstrated a significant frequency of this habit compared with temporomandibular dysfunctions, which are less prevalent in this age group. 12 However, there are studies that have found lower frequencies, ranging from 5.9% 1,20,21 to 11%. 8,15 The origin of these differences regarding childhood bruxism is assumed to potentially be related to the lack of methodological uniformity in the studies, cultural differences existent among countries, 21,22 or even by the variety in the age groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Parasomnias also represent an important complaint, between 6.2 and 14.4%,the more frequent of them being night terrors, somniloquy, enuresis and bruxism. [11][12][13] Respiratory problems during sleep can occur up to 7.5%, 14 while sleep movement disorders, such as restless legs syndrome and periodic limb movement, occur between 2 and 23%. 15,16 Overall, sleep disorders could affect more than 40% of children.…”
Section: Introductionmentioning
confidence: 99%